Personality, age and sex differences in wild and zoo-housed Japanese macaques, Macaca fuscata - Joléne van der Mescht; Miho Inoue-Murayama; Takafumi Suzumura; Lydia M. Hopper; Bonaventura Majolo; Andrew J.J. MacIntosh; Drew M. Altschul; Alexander Weiss (Animal Behaviour, 2026)

Body Size, Dispersal Potential, Range Size and Habitat Fragmentation Are Linked to Extinction Risk of Freshwater Mussels - Garrett W. Hopper; Sean M. Keogh; Carla L. Atkinson; Traci P. DuBose; Jeffrey D. Lozier; John M. Pfeiffer; Irene Sánchez González (Journal of Biogeography, 2026)
Aim Trait‐based approaches are increasingly recognised as tools for understanding species' vulnerabilities to intensifying global change. For species with complex life histories that involve a parasitic life stage, a combination of traits associated with either the host or parasite could influence extinction risk. Location United States of America. Taxon Freshwater mussels are a highly threatened assemblage of bivalves with an obligate ectoparasitic larval stage requiring a host fish. Adult mussels are sedentary, with long‐distance dispersal dictated by the dispersal ability of the host fish during the parasitic larval life phase. Methods We integrate several open‐source spatial and trait datasets for freshwater mussels and host fishes to test hypotheses about the relationship between species‐level traits such as body size, area of occupancy (AOO), host fish dispersal, habitat fragmentation and mussel extinction risk. Results Imperilled mussels were smaller, had smaller areas of occupancy, used small‐bodied, dispersal‐limited host fishes and had higher densities of large dams in their AOO compared to non‐imperilled mussels. Conclusions Body size, along with AOO and dispersal potential, appears to have cascading effects on imperilment where decreases in these traits potentiate population fragmentation via large dams. Thus, in contrast to many other groups, freshwater mussel body size is inversely related to extinction risk, and small‐bodied mussels should be closely monitored to prevent future extinctions.

Biocontrol practitioners’ perspectives on emerging genetic-based technologies for weed management - M. A. Rafter; N. Kumaran; D. R. Brookes; M. K. Reid; K. E. Bowers; A. J. McConnachie; M. Cristofaro; R. F. H. Sforza; B. Gooden; M. Hopper (BioControl, 2026)
Weed biocontrol researchers have been at the forefront of developing management solutions for invasive weeds for over 100 years and have a unique perspective to offer on the emerging field of genetic-based technologies such as gene drive and RNAi. As part of the XVI International Symposium on Biological Control of Weeds in May 2023 we conducted a focus group discussion workshop to explore biocontrol practitioners’ perspectives related to: (1) Genetic-based control technologies, and the factors influencing support (or not) for their application to weed management, especially weed biocontrol, (2) perceived opportunities to apply genetic-based control tools to enhance or complement weed biocontrol, focusing on whether/how genetic tools can be applied to fundamentally change the practice of weed biocontrol, and (3) genetic-based control in weed management and how it can operate within the Access and Benefit Sharing regulatory landscape. We analyse the perspectives of biocontrol scientists from the workshop and discuss the prospects and challenges of integrating novel genetic-based control tools with weed biocontrol.

Scientists’ warning on the global destruction of rock outcrop ecosystems - Luiza F. A. de Paula; Lucas N. Perillo; Gianluigi Ottaviani; Flávio F. Carmo; Mandar N. Datar; Katherine C. Enebeli‐Ekwutoziam; Bruno Fogliani; Stephen D. Hopper; Aboli Kulkarni; Hans Lambers; Rafael F. Magalhães; Frederico S. Neves; et al. (Conservation Biology, 2026)
Rock outcrops are geological formations that harbor a highly specialized biota adapted to harsh environmental conditions that differ from their surrounding landscapes. They are globally distributed, especially in old, highly weathered landscapes, and can function as habitat islands containing high levels of endemism and distinct evolutionary lineages. Despite their ecoevolutionary importance, rock outcrops remain largely overlooked in global conservation policy, ecosystem typologies, and biodiversity monitoring frameworks. Extractive activities directly remove the geological substrate that underpins these habitats, and climate change intensifies drought, heatwaves, and hydrological instability. Rising global demand for energy‐transition metals required for decarbonization is expected to further accelerate these pressures, particularly in biodiverse regions of the Global South where governance is weaker. Given that rock outcrop ecosystems are ecologically and evolutionarily significant, we devised a policy‐relevant conservation roadmap structured around prevention, mitigation, restoration, and governance issues. Priority actions include recognizing rock outcrops as unique ecosystems in global classifications and ecosystem typologies, integrating them into biodiversity monitoring frameworks, and improving the identification of key biodiversity areas and the International Union for Conservation of Nature (IUCN) Red List of Ecosystems assessments. We call for stronger environmental impact assessments, cumulative‐impact evaluations for mining and quarrying projects, and the designation of mining and quarrying exclusion sites of high irreplaceability. Coordinated international policy, improved ecological data, and meaningful engagement with local and Indigenous communities are essential to safeguard these ancient ecosystems before further, irreversible losses occur.

Creating connection: greeting and leave-taking behavior in nonhuman primates - Lydia M. Hopper (Evolution and Human Behavior, 2025)

Can useful biomarker information be obtained from museum fossil specimens treated with Paraloid® B-72 acrylic resin? - Luke M. Brosnan; Stephen F. Poropat; Madison Tripp; Sebastian Stanley; Peter Hopper; Xiao Sun; William D.A. Rickard; Antônio Á.F. Saraiva; Renan A.M. Bantim; Juliana M. Sayão; Alexander W.A. Kellner; Kliti Grice (Organic Geochemistry, 2025)

A global meta‐analysis of ecological functions and regulating ecosystem services of freshwater bivalves - Alexandra Zieritz; Joshua I. Brian; Ronaldo Sousa; David C. Aldridge; Carla L. Atkinson; Karel Douda; Caryn Vaughn; Yulia Bespalaya; Tabitha Richmond; Adam M. Ćmiel; Alma Crisp; Andreas H. Dobler; et al. (Limnology and Oceanography, 2025)
Freshwater bivalves are globally distributed, diverse, and common in benthic communities. Many taxa, particularly in the most species‐rich order, Unionida, are declining due to anthropogenic stressors, while a small number of non‐native species have become increasingly abundant and widespread, commonly replacing native bivalve assemblages. To understand how these global changes may impact ecosystems and people, we conducted a meta‐analysis of existing literature quantifying the ecological functions (= supporting or intermediate ecosystem services) and regulating ecosystem services of freshwater bivalves (hereafter “ecosystem services”). Random effects meta‐analysis modeling across 447 case studies revealed a positive effect on human health, safety, or comfort of freshwater bivalve ecosystem services overall and specifically, via effects on native macrofauna, microorganisms, wastes, and pollutants, and the physico‐chemical condition or quantity of sediments. Generally, effects of native species and species within the orders Unionida and Venerida were more significant and positive than those of other freshwater bivalves. No significant overall effect was found for ecosystem services related to zooplankton, algae, invasive species, and the physico‐chemical condition of ambient water. Moreover, a significant bias toward publication of positive results existed for studies quantifying ecosystem services related to algae. These findings illustrate the global importance of the ecosystem services of freshwater bivalves and highlight the need for large‐scale conservation and restoration efforts for their species and populations globally, including those of common species. Our findings also question common assumptions of strong and ubiquitous effects of freshwater bivalves on algae and water condition, cautioning against extrapolating observations across systems.

Fossilisation of Fish Soft Tissue in Oxidative Microniches of Anoxic Sediments - Amy L. Elson; Lorenz Schwark; Paul F. Greenwood; Madison Tripp; Alex I. Holman; Michael E. Böttcher; Peter Hopper; Robert H. C. Madden; Luke M. Brosnan; Jessica H. Whiteside; Stephen F. Poropat; Lance Grande; et al. (Environmental Microbiology, 2025)
Organic analyses of past organisms enhance our understanding of Earth's evolutionary history, complementing the macrofossil record. Biomolecular remains are typically vulnerable to diagenetic mineralisation, but can persist in exceptional depositional settings such as Lagerstätten. Their preservation is usually linked to anoxic conditions that exclude aerobic degraders. However, we report intact skin tissue of the fossil fish Diplomystus dentatus from the Fossil Basin Lagerstätte (USA), preserved through phosphate permineralisation in an oxygen‐enriched microenvironment. Notably, only the skin with scales retained tissue integrity, and this organic material was closely associated with fluorapatite absent from the surrounding matrix. Geochemical analyses revealed higher oxidation states in the skin than in vertebrae and bones, likely due to early degradation of the fatty acid‐rich dermis. Redox‐sensitive biomarkers and isotopic data (δ 15 N) indicated a less reducing environment in the skin region compared to bones and the eye, yet more reducing than the surrounding sediment. This localised oxygen enrichment fostered sulphide‐oxidising bacteria, evidenced by mineral sulphates (barite) found only in the skin. Phosphatisation was likely driven by dermal breakdown and the release of H+, reducing alkalinity and enabling phosphate mineralisation over the carbonate system.

Procedural Variation May Contribute to 6-Minute Walk Distance Variability in Real-World Pediatric Pulmonary Arterial Hypertension Study - Cynthia Kleppinger; Dunbar Ivy; Norman Stockbridge; Angela Bates; Stephanie Handler; Usha S. Krishnan; Mary P. Mullen; Delphine Yung; Rachel K. Hopper; Nidhy P. Varghese; Jeff Fineman; Eric D. Austin; et al. (The AAPS Journal, 2025)
The six-minute walk test (6MWT) is a common method to assess submaximal exercise capacity in children and adults with pulmonary arterial hypertension (PAH) and other chronic diseases. There is no guideline specifically for 6MWT in children. In this observational pilot study, we evaluated the impact of procedural variations on the outcome of the 6MWT in the real-world clinical setting at pediatric PAH programs. We collected 6MWT data from 33 children with PAH participating in a multicenter, prospective, non-interventional study. Data range/quantiles and standard deviation (SD) were used to describe distribution of the six-minute walk distance (6MWD) and data variability. Levene’s test was used to test for heterogeneity of variance with the two sites of similar altitude and their age/height/weight-matched Panama Function Class II participants. We analyzed all 33 eligible participants and their qualified first walks at five centers (A-E) with 6MWD ranges of 420–570, 357–683, 418–481, 400–700, 377–549 m, respectively. Site D performed the 6MWT in a busy hallway and allowed parental/caregiver’s cheering, while Site E performed the 6MWT in a secluded area with no parental/caregiver involvement. Mean 6MWD and SD for Sites D and E were 547 (125) and 432 (67.5) meters, respectively (p = 0.03). In conclusion, procedural variations seem to associate with 6MWD data variability. Although interpretation of our results is limited by the small sample size, our findings suggest that standardizing pediatric 6MWT procedures are needed. Graphical Abstract

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Protocols to assist deconvolution of co-eluting 5β– and 5α–steranes by gas chromatography–mass spectrometry - Luke M. Brosnan; Paul F. Greenwood; Peter Hopper; Kliti Grice (Organic Geochemistry, 2025)

Internal organs and body tissues of free-swimming whale sharks (Rhincodon typus) imaged using underwater ultrasound - M. G. Meekan; F. Thompson; K. Brooks; R. Matsumoto; K. Murakumo; E. Lester; A. Dove; B. Hopper (Frontiers in Marine Science, 2024)
Ultrasound imaging can be used as an effective tool to measure the reproductive status and condition of sharks. This usually requires restraint of the subject, which is not feasible in the wild when the target species is of conservation concern and very large, as is the case for whale sharks. Our study invoked a behavioral response in free-swimming whale sharks that allowed snorkelers to image internal organs and structures using a submersible ultrasound scanner linked to an iPhone in an underwater housing. We were able to reliably locate and monitor the heart and other internal organs inside the body cavity, structures inside the head, and image skin and muscle in the dorsal surface of the sharks. The technique is evaluated as a means for assessing the condition and reproductive status of free-swimming whale sharks.

Equations for early-stage design embodied carbon estimation for concrete floors of varying loading and strength - Jonathan M. Broyles; Juan Pablo Gevaudan; Michael W. Hopper; Ryan L. Solnosky; Nathan C. Brown (Engineering Structures, 2024)

Assessment of the embodied carbon performance of post-tensioned voided concrete plates as a sustainable floor solution in multi-story buildings - Jonathan M. Broyles; Michael W. Hopper (Engineering Structures, 2023)

Correction to: An evaluation of thermal imaging as a welfare monitoring tool for captive chimpanzees - Stephen R. Ross; Benjamin R. Lake; Amy Fultz; Lydia M. Hopper (Primates, 2021)

An evaluation of thermal imaging as a welfare monitoring tool for captive chimpanzees - Stephen R. Ross; Benjamin R. Lake; Amy Fultz; Lydia M. Hopper (Primates, 2021)

Traits related to efficient acquisition and use of phosphorus promote diversification in Proteaceae in phosphorus‐impoverished landscapes - Patrick E. Hayes; Francis J. Nge; Michael D. Cramer; Patrick M. Finnegan; Peili Fu; Stephen D. Hopper; Rafael S. Oliveira; Benjamin L. Turner; Graham Zemunik; Hongtao Zhong; Hans Lambers (Plant and Soil, 2021)

Do the risks of Lynch syndrome-related cancers depend on the parent of origin of the mutation? - Shimelis Dejene Gemechu; Christine M. van Vliet; Aung Ko Win; Jane C. Figueiredo; Loic Le Marchand; Steven Gallinger; Polly A. Newcomb; John L. Hopper; Noralane M. Lindor; Mark A. Jenkins; James G. Dowty (Familial Cancer, 2020)

Correction to: Using a Touchscreen Paradigm to Evaluate Food Preferences and Response to Novel Photographic Stimuli of Food in Three Primate Species (Gorilla gorilla gorilla, Pan troglodytes, and Macaca fuscata) - Sarah M. Huskisson; Sarah L. Jacobson; Crystal L. Egelkamp; Stephen R. Ross; Lydia M. Hopper (International Journal of Primatology, 2020)

Using a Touchscreen Paradigm to Evaluate Food Preferences and Response to Novel Photographic Stimuli of Food in Three Primate Species (Gorilla gorilla gorilla, Pan troglodytes, and Macaca fuscata) - Sarah M. Huskisson; Sarah L. Jacobson; Crystal L. Egelkamp; Stephen R. Ross; Lydia M. Hopper (International Journal of Primatology, 2020)

Body size and dietary risk factors for aggressive prostate cancer: a case–control study - Mikaela Pal; Allison M. Hodge; Nathan Papa; Robert J. MacInnis; Julie K. Bassett; Damien Bolton; Ian D. Davis; Jeremy Millar; Dallas R. English; John L. Hopper; Gianluca Severi; Melissa C. Southey; et al. (Cancer Causes & Control, 2019)

Ability of known susceptibility SNPs to predict colorectal cancer risk for persons with and without a family history - Mark A. Jenkins; Aung K. Win; James G. Dowty; Robert J. MacInnis; Enes Makalic; Daniel F. Schmidt; Gillian S. Dite; Mirosl Kapuscinski; Mark Clendenning; Christophe Rosty; Ingrid M. Winship; Jon D. Emery; et al. (Familial Cancer, 2019)

Lifetime alcohol intake and pancreatic cancer incidence and survival: findings from the Melbourne Collaborative Cohort Study - Harindra Jayasekara; Dallas R. English; Allison M. Hodge; Robin Room; John L. Hopper; Roger L. Milne; Graham G. Giles; Robert J. MacInnis (Cancer Causes & Control, 2019)

Foraging in a social setting: a comparative analysis of captive gorillas and chimpanzees - Kristin E. Bonnie; Laura M. Bernstein-Kurtycz; Marisa A. Shender; Stephen R. Ross; Lydia M. Hopper (Primates, 2019)

Assessing patient readiness for personalized genomic medicine - Caren J. Frost; Irene L. Andrulis; Saundra S. Buys; John L. Hopper; Esther M. John; Mary Beth Terry; Angela Bradbury; Wendy K. Chung; Katherine Colbath; Natalie Quintana; Elizabeth Gamarra; Brian Egleston; et al. (Journal of Community Genetics, 2019)

A probe-based quantitative PCR assay for detecting Tetracapsuloides bryosalmonae in fish tissue and environmental DNA water samples - Patrick R. Hutchins; Adam J. Sepulveda; Renee M. Martin; Lacey R. Hopper (Conservation Genetics Resources, 2018)

Somatic mutations of the coding microsatellites within the beta-2-microglobulin gene in mismatch repair-deficient colorectal cancers and adenomas - Mark Clendenning; Alvin Huang; Harindra Jayasekara; Marie Lorans; Susan Preston; Neil O’Callaghan; Bernard J. Pope; Finlay A. Macrae; Ingrid M. Winship; Roger L. Milne; Graham G. Giles; Dallas R. English; et al. (Familial Cancer, 2018)

Improved quality of risk-reducing salpingo-oophorectomy in Australasian women at high risk of pelvic serous cancer - Y. C. Lee; M. Bressel; P. Grant; P. Russell; C. Smith; S. Picken; S. Camm; B. E. Kiely; R. L. Milne; S. A. McLachlan; M. Hickey; M. L. Friedlander; et al. (Familial Cancer, 2017)

Is breast cancer risk associated with alcohol intake before first full-term pregnancy? - Harindra Jayasekara; Robert J. MacInnis; Allison M. Hodge; Robin Room; Roger L. Milne; John L. Hopper; Graham G. Giles; Dallas R. English (Cancer Causes & Control, 2016)

Estimating cumulative risks for breast cancer for carriers of variants in uncommon genes - Noralane M. Lindor; John Hopper; James Dowty (Familial Cancer, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Determining the familial risk distribution of colorectal cancer: a data mining approach - Rowena Chau; Mark A. Jenkins; Daniel D. Buchanan; Driss Ait Ouakrim; Graham G. Giles; Graham Casey; Steven Gallinger; Robert W. Haile; Loic Le Marchand; Polly A. Newcomb; Noralane M. Lindor; John L. Hopper; et al. (Familial Cancer, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Risk of colorectal cancer for people with a mutation in both a MUTYH and a DNA mismatch repair gene - Aung Ko Win; Jeanette C. Reece; Daniel D. Buchanan; Mark Clendenning; Joanne P. Young; Sean P. Cleary; Hyeja Kim; Michelle Cotterchio; James G. Dowty; Robert J. MacInnis; Katherine M. Tucker; Ingrid M. Winship; et al. (Familial Cancer, 2015)

Childhood cancers in families with and without Lynch syndrome - John A. Heath; Jeanette C. Reece; Daniel D. Buchanan; Graham Casey; Carol A. Durno; Steven Gallinger; Robert W. Haile; Polly A. Newcomb; John D. Potter; Stephen N. Thibodeau; Loïc Le Marchand; Noralane M. Lindor; et al. (Familial Cancer, 2015)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Variation in plant diversity in mediterranean‐climate ecosystems: the role of climatic and topographical stability - Richard M. Cowling; Alastair J. Potts; Peter L. Bradshaw; Jonathan Colville; Margarita Arianoutsou; Simon Ferrier; Felix Forest; Nikolaos M. Fyllas; Stephen D. Hopper; Fernando Ojeda; Şerban Procheş; Rhian J. Smith; et al. (Journal of Biogeography, 2015)
Aim Although all five of the major mediterranean‐climate ecosystems ( MCE s) of the world are recognized as loci of high plant species diversity and endemism, they show considerable variation in regional‐scale richness. Here, we assess the role of stable Pleistocene climate and Cenozoic topography in explaining variation in regional richness of the globe's MCE s. We hypothesize that older, more climatically stable MCE s would support more species, because they have had more time for species to accumulate than MCE s that were historically subject to greater topographic upheavals and fluctuating climates. Location South‐western Africa (Cape), south‐western Australia, California, central Chile and the eastern (Greece) and western (Spain) Mediterranean Basin. Methods We estimated plant diversity for each MCE as the intercepts of species–area curves that are homogeneous in slope across all regions. We used two down‐scaled global circulation models of the Last Glacial Maximum ( LGM ) to quantify climate stability by comparing the change in the location of MCE s between the LGM and present. We quantified the Cenozoic topographic stability of each MCE by comparing contemporary topographic profiles with those present in the late Oligocene and the early Pliocene. Results The most diverse MCE s – Cape and Australia – had the highest Cenozoic environmental stability, and the least diverse – Chile and California – had the lowest stability. Main conclusions Variation in plant diversity in MCE s is likely to be a consequence not of differences in diversification rates, but rather the persistence of numerous pre‐Pliocene clades in the more stable MCE s. The extraordinary plant diversity of the Cape is a consequence of the combined effects of both mature and recent radiations, the latter associated with increased habitat heterogeneity produced by mild tectonic uplift in the Neogene.

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Lifetime alcohol consumption and upper aero-digestive tract cancer risk in the Melbourne Collaborative Cohort Study - Harindra Jayasekara; Robert J. MacInnis; Allison M. Hodge; John L. Hopper; Graham G. Giles; Robin Room; Dallas R. English (Cancer Causes & Control, 2015)

High prevalence of mismatch repair deficiency in prostate cancers diagnosed in mismatch repair gene mutation carriers from the colon cancer family registry - Christophe Rosty; Michael D. Walsh; Noralane M. Lindor; Stephen N. Thibodeau; Erin Mundt; Steven Gallinger; Melyssa Aronson; Aaron Pollett; John A. Baron; Sally Pearson; Mark Clendenning; Rhiannon J. Walters; et al. (Familial Cancer, 2014)

Cu(I)Cl-promoted synthesis of novel N-alkylated isatin analogs with an extension toward isatin-4-aminoquinoline conjugates: in vitro analysis against Trichomonas vaginalis - Nisha; Richard Tran; Donald Yang; Dominique Hall; Melissa J. Hopper; Lisa A. Wrischnik; Kirkwood M. Land; Vipan Kumar (Medicinal Chemistry Research, 2014)

Reduced parasite diversity and abundance in a marine whelk in its expanded geographical range - Julie V. Hopper; Armand M. Kuris; Julio Lorda; Sara E. Simmonds; Crow White; Ryan F. Hechinger (Journal of Biogeography, 2014)
Aim To improve our understanding of how parasitism interacts with geographical range expansions by quantifying diversity and abundance of parasites in 25 populations of a large marine snail, Kellet's whelk ( Kelletia kelletii ), throughout its historical and recently expanded range, which are separated by a well‐known biogeographical boundary. Location California coast (western North America). Methods Parasitological examinations were conducted on 199 whelks from 25 subtidal reefs throughout its expanded and historical ranges. We calculated infection risk, parasite intensity, and parasite species diversity. Abiotic (temperature, latitude, distance from range limit) and biotic (host density) variables were analysed as potential drivers of differential parasitism between expanded‐ and historical‐range populations. Results Compared with historical‐range whelks, expanded‐range whelks were 20% as likely to be infected by parasites, and those that were infected had 6% the number of individual parasites. On average, expanded‐range whelks had 14% the number of parasite species than the historical‐range whelks. The marked decrease in species richness of parasites infecting expanded‐range whelks was only partly explained by the low numbers of parasites. The reduced parasite abundance and diversity in the expanded‐range whelks was not explained by the examined abiotic factors or by whelk density. Main conclusions Expanded‐range populations of Kellet's whelk experience substantially lower parasite abundance and diversity than the historical‐range populations, despite relatively poor demographic performance. The reduced parasitism observed resembles the enemy escape typically characterizing invasive species. A possible explanation for the observed ‘parasite escape’ is that the biogeographical boundary limits the movements or drives the low abundance of other host species (elasmobranchs) required to complete the life cycles of the ‘missing’ parasites. We suggest that parasite escape may generally characterize range‐margin expansions and be important in permitting expansions into what may otherwise be marginal habitats. This parasite escape may directly counter the spread of infectious diseases associated with global warming‐induced range shifts.

Synthesis and preliminary in vitro activity of mono- and bis-1H-1,2,3-triazole-tethered β-lactam–isatin conjugates against the human protozoal pathogen Trichomonas vaginalis - Raghu Raj; Vaishali Sharma; Melissa J. Hopper; Neal Patel; Dominique Hall; Lisa A. Wrischnik; Kirkwood M. Land; Vipan Kumar (Medicinal Chemistry Research, 2014)

How do researchers manage genetic results in practice? The experience of the multinational Colon Cancer Family Registry - Louise A. Keogh; Douglass Fisher; Sherri Sheinfeld Gorin; Sheri D. Schully; Jan T. Lowery; Dennis J. Ahnen; Judith A. Maskiell; Noralane M. Lindor; John L. Hopper; Terrilea Burnett; Spring Holter; Julie L. Arnold; et al. (Journal of Community Genetics, 2014)

The Next Direction for Primatology? A Commentary on Setchell (2013) - Lydia M. Hopper; David B. Morgan; Stephen R. Ross (International Journal of Primatology, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Dietary intake of B vitamins and methionine and breast cancer risk - Julie K. Bassett; Laura Baglietto; Allison M. Hodge; Gianluca Severi; John L. Hopper; Dallas R. English; Graham G. Giles (Cancer Causes & Control, 2013)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Dietary intake of B vitamins and methionine and prostate cancer incidence and mortality - Julie K. Bassett; Gianluca Severi; Allison M. Hodge; Laura Baglietto; John L. Hopper; Dallas R. English; Graham G. Giles (Cancer Causes & Control, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Adequacy of risk-reducing gynaecologic surgery in BRCA1 or BRCA2 mutation carriers and other women at high risk of pelvic serous cancer - B. E. Kiely; M. L. Friedlander; R. L. Milne; L. Stanhope; P. Russell; M. A. Jenkins; P. Weideman; S. A. McLachlan; P. Grant; J. L. Hopper; K. A. Phillips (Familial Cancer, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

The Role of Botanic Gardens in the Science and Practice of Ecological Restoration - KATE A. HARDWICK; PEGGY FIEDLER; LYNDON C. LEE; BRUCE PAVLIK; RICHARD J. HOBBS; JAMES ARONSON; MARTIN BIDARTONDO; ERIC BLACK; DAVID COATES; MATTHEW I. DAWS; KINGSLEY DIXON; STEPHEN ELLIOTT; et al. (Conservation Biology, 2011)
Many of the skills and resources associated with botanic gardens and arboreta, including plant taxonomy, horticulture, and seed bank management, are fundamental to ecological restoration efforts, yet few of the world's botanic gardens are involved in the science or practice of restoration. Thus, we examined the potential role of botanic gardens in these emerging fields. We believe a reorientation of certain existing institutional strengths, such as plant‐based research and knowledge transfer, would enable many more botanic gardens worldwide to provide effective science‐based support to restoration efforts. We recommend botanic gardens widen research to include ecosystems as well as species, increase involvement in practical restoration projects and training practitioners, and serve as information hubs for data archiving and exchange.

Physical activity, body size and composition, and risk of ovarian cancer - Fiona Chionh; Laura Baglietto; Kavitha Krishnan; Dallas R. English; Robert J. MacInnis; Dorota M. Gertig; John L. Hopper; Graham G. Giles (Cancer Causes & Control, 2010)

Genes involved with folate uptake and distribution and their association with colorectal cancer risk - Jane C. Figueiredo; A. Joan Levine; Won H. Lee; David V. Conti; Jenny N. Poynter; Peter T. Campbell; David Duggan; Juan Pablo Lewinger; Maria Elena Martinez; Cornelia M. Ulrich; Polly Newcomb; John Potter; et al. (Cancer Causes & Control, 2010)

Is MSH2 a breast cancer susceptibility gene? - EE Ming Wong; Andrea A. Tesoriero; Gulietta M. Pupo; Margaret R. E. McCredie; Graham G. Giles; John L. Hopper; Graham J. Mann; David E. Goldgar; Melissa C. Southey (Familial Cancer, 2008)

Predicting BRCA1 and BRCA2 gene mutation carriers: comparison of LAMBDA, BRCAPRO, Myriad II, and modified Couch models - Noralane M. Lindor; Rachel A. Lindor; Carmel Apicella; James G. Dowty; Amanda Ashley; Katherine Hunt; Betty A. Mincey; Marcia Wilson; M. Cathie Smith; John L. Hopper (Familial Cancer, 2007)

Body size and composition and risk of rectal cancer (Australia) - Robert J. MacInnis; Dallas R. English; Andrew M. Haydon; John L. Hopper; Dorota M. Gertig; Graham G. Giles (Cancer Causes & Control, 2006)

Antidepressant-like effects of PDE4 inhibitors mediated by the high-affinity rolipram binding state (HARBS) of the phosphodiesterase-4 enzyme (PDE4) in rats - Han-Ting Zhang; Yu Zhao; Ying Huang; Chengjun Deng; Allen T. Hopper; Michael De Vivo; Gregory M. Rose; James M. O’Donnell (Psychopharmacology, 2006)

Effects of the novel PDE4 inhibitors MEM1018 and MEM1091 on memory in the radial-arm maze and inhibitory avoidance tests in rats - Han-Ting Zhang; Ying Huang; Neesha U. Suvarna; Chengjun Deng; Alicia M. Crissman; Allen T. Hopper; Michael De Vivo; Gregory M. Rose; James M. O’Donnell (Psychopharmacology, 2005)

Foods, nutrients and prostate cancer - Allison M. Hodge; Dallas R. English; Margaret R.E. McCredie; Gianluca Severi; Peter Boyle; John L. Hopper; Graham G. Giles (Cancer Causes & Control, 2004)

Abuse liability assessment of sibutramine, a novel weight control agent - L. M. Schuh; C. R. Schuster; J. A. Hopper; C. M. Mendel (Psychopharmacology, 2000)

Monocrotophos-Induced Mass Mortality of Swainson's Hawks in Argentina, 1995–96 - Michael I. Goldstein; T. E. Lacher; B. Woodbridge; M. J. Bechard; S. B. Canavelli; M. E. Zaccagnini; G. P. Cobb; E. J. Scollon; R. Tribolet; M. J. Hopper (Ecotoxicology, 1999)

Landslides in the Lower Greensand escarpment in south Kent - E. N. Bromhead; A. C. Hopper; M.-L. Ibsen (Bulletin of Engineering Geology and the Environment, 1998)